The Occupational History of the Bronze Age Harbour City of Hala Sultan Tekke, Cyprus - Fischer, Peter M. (Ägypten und Levante, 2020)
The present paper is a synthesis of nine seasons of excavations supported by geophysical surveys at the Late Bronze Age harbour city of Hala Sultan Tekke near Larnaca on the southern littoral of Cyprus. Conclusions and hypotheses dealing with the origin, the heydays and the decline of this eastern Mediterranean trade metropolis are presented in addition to a summary of the previous field reports. A summary of the results from excavations in the recently discovered extramural cemetery with numerous rich tombs, offering pits and wells is included. The city’s vast intercultural relationships, which are based on trade, and chronological and terminological issues are particularly considered. Special attention is devoted to the final decades of the life cycle of this city which fall into the period of years of a widespread crisis at the waning Bronze Age, characterised by the ‘Sea Peoples Phenomenon.